1982
DOI: 10.1227/00006123-198208000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Chondromyxoid Fibroma of the Cervical Spine—a Case Report with a Review of the Literature and a Description of an Operative Approach to the Lower Anterior Cervical Spine

Abstract: A case of chondromyxoid fibroma arising from the C-7 vertebral body and involving the epidural space and paraspinal soft tissues is presented. The surgical treatment of this tumor is described, and the pertinent literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…They described a 34-year-old female patient with involvement of the spine with CMF at the T 2 –T 3 level. Additional spinal cases of CMF were reported by Gusdcha [10], Spjut et al [11], Schajowicz and Gallardo [12], Rahimi et al [13], Ramani [14], Torma [15], Dahlin [8], Mayer [16], Merli et al [17], Nunez et al [6], Standefer et al [5]and Schajowicz [18]. Compared to the many hundreds of cases of CMF in the literature involving the skeletal system, Mirra et al [19](in a review of 400 cases of CMF) rightly pointed out that this tumor is rare in the spine.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…They described a 34-year-old female patient with involvement of the spine with CMF at the T 2 –T 3 level. Additional spinal cases of CMF were reported by Gusdcha [10], Spjut et al [11], Schajowicz and Gallardo [12], Rahimi et al [13], Ramani [14], Torma [15], Dahlin [8], Mayer [16], Merli et al [17], Nunez et al [6], Standefer et al [5]and Schajowicz [18]. Compared to the many hundreds of cases of CMF in the literature involving the skeletal system, Mirra et al [19](in a review of 400 cases of CMF) rightly pointed out that this tumor is rare in the spine.…”
Section: Discussionmentioning
confidence: 95%
“…In a 1978 review of 6,221 bone tumors, Dahlin [4]considered CMF to represent the ‘least common benign tumor derived from cartilage’ with an incidence of less than 0.5% of bone tumors. Standefer et al [5]also found that CMF constitutes only 0.5% of bone tumors. Nunez et al [6], as well as Dorfman and Cherniak [7], also considered them to be quite rare: ‘less than 1% of primary bone tumors’.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standefer et al [18] use a more classical technique, which involves biclavicular osteotomy combined with sternal splitting. The midline sternal splitting approach is the most extensile procedure, and provides exposure down to T4.…”
Section: Discussionmentioning
confidence: 99%
“…Standefer et al, 20 reported that the benign radiological appearance of CMF at more common sites may not be entirely analagous to vertebral lesions. Features particular to vertebral CMF include extensive erosion of the bony cortex, even beyond the confines of the periosteum into surrounding soft tissue or spinal canal which may be severe enough to suggest malignant destruction.…”
Section: Spinal Chondromyxoid Fibromamentioning
confidence: 99%